The Impact of Transurethral Enucleation Therapeutic Approach in All-Size Benign Prostatic Obstruction Pathology: From Contemporary Technological Advances to Evidence-Based Clinical Progresses - Catalin-Andrei Bulai; Razvan-Dragos Multescu; Petrisor-Aurelian Geavlete; Ana Maria Andreea Punga; Adrian Militaru; Bogdan-Gabriel Buzescu; Cosmin-Victor Ene; Cristian Mares; Bogdan-Florin Geavlete (Diagnostics)
Transurethral enucleation (TUE) has revolutionized the management of benign prostatic obstruction (BPO), offering a minimally invasive solution with superior efficacy across all prostate sizes. This review explores the advancements in TUE techniques, including Holmium Laser Enucleation of the Prostate (HoLEP), Thulium Laser Enucleation of the Prostate (ThuLEP), and bipolar enucleation, highlighting their clinical benefits, safety profiles, and long-term outcomes. Compared to traditional approaches such as transurethral resection of the prostate (TURP) and open prostatectomy, TUE has been associated with reduced complication rates, shorter recovery times, and durable symptom relief. The manuscript also examines patient-centered considerations, such as quality of life improvements and preservation of sexual function, which contribute to high patient satisfaction. Furthermore, the economic advantages of TUE, driven by reduced retreatment rates and healthcare costs, underscore its value for both patients and healthcare systems. Emerging innovations, including artificial intelligence (AI), promise to further enhance procedural planning, surgical precision, and training pathways. Efforts to expand global access through cost-effective adaptations like bipolar enucleation and targeted training initiatives are paving the way for wider adoption of TUE. With its adaptability, technological advancements, and focus on patient outcomes, TUE is poised to become the global standard of care in BPO management.